Bears - Rosenthal, Mark, 1946- (Chicago : Childrens Press, 1983)
Briefly describes the different kinds of bears, how they behave, and how they should be treated.
Includes index.
Elem. School Library Collection.
3.0
K-3
Keywords: Bears -- Juvenile literature; Bears; Bears; Bears